Demographic and Clinical Profile of Anterior Uveitis Patients Presenting in a Tertiary Eye Care Hospital - Chandravanshi, Shivcharan Lal (International Journal of Innovative Research in Medical Science, 2018)
Introduction - Anterior uveitis is referred as an inflammation of the iris and ciliary body. Anterior uveitis is the most common type of uveitis and frequently affecting young adults. Aim of this study was to evaluate the clinical presentation, etiology, pathological pattern, complications and treatment outcome of anterior uveitis in the Rewa district of Madhya Pradesh. Materials and Methods - A Prospective, hospital based, interventional study was conducted on all anterior uveitis patients, treated at the Department of ophthalmology, S. S. Medical College, Rewa, Madhya Pradesh for the period of two years from January 2016 to December 2017. All patients aged 0-80 years that were treated for anterior uveitis are taken in consideration. Complete ophthalmic evaluation, necessary lab investigations and imaging were performed to establish the etiology. Demographic data, uveitis characteristics, pathological pattern, investigations, etiology, complications and the treatment outcome were collected for each patient. Patients of anterior uveitis with incomplete investigations, intermediate, posterior and panuveitis, postoperative uveitis, sympathetic ophthalmia, endophthalmitis and masquerade syndromes were excluded from study. Results - Present study included 212 patients over a period of two years (January 2016 to December 2017). Anterior uveitis affect most frequently in the 5th decade of life (33.96%). Majority of patients had non-granulomatous type of uveitis (73.11%). Etiology of anterior uveitis remained unknown (idiopathic) in 126 cases (59.43%). The most common etiology identify in present study is tuberculosis in 47 cases (22.16%) followed by syphilis in 8 cases (3.77%). The most common complication of anterior uveitis is complicated cataract 18 cases (8.49%) followed by secondary glaucoma in 8 cases (3.77%). Conclusion - This study gives valuable information on clinical and demographic characteristics of anterior uveitis in resident of the Rewa, district of Madhya Pradesh.